Faktor-Faktor Yang Mempengaruhi Perencanaan Keuangan Keluarga - Yayu Kusdiana; Safrizal Safrizal (LPPM ISNJ Bengkalis, 2022)
This study aims to show the effect of financial literacy, education level, and income level on family financial planning in Banjar Balam village, Lirik sub-district, Indragiri Hulu regency, and Riau province. The research method was developed quantitatively. The population of this study was all heads of families in the Banjar Balam village, as many as 504 people. The sampling technique used purposive sampling in order to obtain 80 samples. Research shows that financial literacy and income level positively and significantly affect family financial planning. In contrast, the level of education does not affect family financial planning. Simultaneously financial literacy, education level, and income level significantly affect family financial planning by 34 percent. This research can be a reference for local governments in disseminating family financial planning in Indragiri Hulu regency.